Research Progress of Microglia Involved in Neuropathic Pain in Recent Ten Years —-Bibliometric Analysis Based on CiteSpace - 黄雄; 周蔚 (Pacific International Journal, 2025)
Based on CiteSpace, this study performed a bibliometric analysis of 400 articles (100 English, 300 Chinese) from PubMed and CNKI (2015–2025) to investigate the role of microglia in neuropathic pain (NP). The findings reveal a growing volume of literature in this field, with neuroinflammation representing a major research focus. Keyword analysis identified "neuroinflammation" (Chinese frequency: 62, centrality: 0.55) and "neuropathic pain" (English frequency: 60, centrality: 0.51) as the most representative terms. Microglia modulate inflammatory responses via M1/M2 polarization, involving channels such as TRPV4 and VRAC, and signaling pathways including CXCL13 and NLRP3, playing a central role in NP development. Future research should further elucidate microglial heterogeneity and immune regulatory mechanisms to identify novel therapeutic targets for NP.